Development of Interactive Learning Videos to Improve Students' Mathematical Literacy Skills - Ahmad Farham Majid; Ashar Mubarak; Arni Aulia; Resa Yulianti; Khairullah Irsyad Saleh (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Mathematical literacy skills are very necessary for facing the challenges of the 21st century. Developing learning videos that link mathematical material to its implementation in everyday life. This research aims to: 1) develop interactive video learning media toimprove students' mathematical literacyskills; 2) determinethe feasibility of learningvideo media based onexperts and students; and 3) determine the effectiveness of interactive learning videos in improving students' mathematical literacy skills. This research uses a typeof research and development(R&D) that was developed using the modified ASSUREmodel by only applying four of the six development steps, namely: 1)analysing; 2)statingobjectives; 3) selecting methods, media, and materials; and 4)utilising media. The results of the research are: 1)The media developed is an interactive learning video to improve students' mathematical literacy skills, which can be accessed at https://youtu.be/ZxHBMp1etEI?si=GJOtQZPKr5A2D4sK. and https://youtu.be/WvGdq0VQ0mQ?si= SpSZd-l0tjIegH_e. 2)The validation results of the media experts developed were 91.25% in the very good category; 3)the media material validation results were 91.25% in the very good category; 4)students' mathematical literacy skills increased in the medium category with an N-Gain value of 0.61. Thus, interactive learning videos are suitable to be used to improve students' mathematical literacy skills.